Audit committee characteristics and earnings management: is there link? - Puwanenthiren, Pratheepkanth (Faculty of Management Studies & Commerce, University of Jaffna, 2018)
This study analyses the correlation between audit committee (AC) characteristics and earnings management in a sample of 100 Sri Lankan firms. The analysed AC characteristics include Size of AC, AC independence, AC knowledge and Frequency of AC meetings. The empirical evidence is provided by a sample of 100 Sri Lankan listed firms. Descriptive statistics and multivariate regression are performed. Evidence suggests that size of AC, AC independence and frequency of AC meetings are significant to reduce the earnings management. The remaining AC characteristics (i.e., AC knowledge) are not found to have a significant impact on the earnings management. Other than that, performance also found to be significant, a finding that is consistent with the previous literature on earnings management. This study provides further evidence on how AC characteristics affect their ability to oversee earnings management.
Keywords: Audit committee; corporate governance; earnings management